PUKAR: an "Alice" in Wonderland. Issue 2 (16th April 2015) - Tiwari, Shalini Rahul; Chopra, Rakesh
Abstract : Subject area: Social Entrepreneurship/management of non-profit organizations (and non-government organizations). Study level/applicability: Undergraduate/MBA/Executive MBA. Case overview: PUKAR is a niche non-government organization (NGO) working on a unique concept of "Right to Research". It has several themes aimed at democratizing research and broadening access to knowledge among the disenfranchised or the weakly institutionalized groups. The resulting output is disseminated through media such as lectures, Web site, books and newsletters, thus initiating local, national and global debates about future of these groups. PUKAR conceptualizes all projects around this philosophy, which are supported by few specialized funding organizations. Funding organizations, on the other hand, are trying to support many causes aimed at improving the quality of life of citizens of various countries. Thus, PUKAR's growth is constrained by limited funds. Nevertheless, PUKAR has been able to create transformation in the lives of youth who carry out these projects. PUKAR, therefore, faces a continuous challenge of conceptualizing proposals that are meaningful and impactful for the society and to stay true to its core philosophy. Expected learning outcomes: The expected learning outcomes include: to understand the nature of challenges (both strategic and operational) faced by a niche NGO; to analyze how the strategy of an NGO evolves with time; to analyze the impediments of growth for a niche NGO; and to analyze the strategic options for growth and sustenance of an NGO. Supplementary materials: Teaching notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes.